New version of midpoint-type inequalities for co-ordinated convex functions via generalized conformable integrals - Mehmet Eyüp Kiriş; Miguel Vivas-Cortez; Tuğba Yalçin Uzun; Gözde Bayrak; Hüseyin Budak (Boundary Value Problems, 2024)
Abstract In the current research, some midpoint-type inequalities are generalized for co-ordinated convex functions with the help of generalized conformable fractional integrals. Moreover, some findings of this paper include results based on Riemann–Liouville fractional integrals and Riemann integrals.